Three near-complete genome assemblies reveal substantial centromere dynamics from diploid to tetraploid in Brachypodium genus - Chen, Chuanye; Wu, Siying; Sun, Yishuang; Zhou, Jingwei; Chen, Yiqian; Zhang, Jing; Birchler, James A.; Han, Fangpu; Yang, Ning; Su, Handong (Genome Biology, 2024)
Centromeres are critical for maintaining genomic stability in eukaryotes, and their turnover shapes genome architectures and drives karyotype evolution. However, the co-evolution of centromeres from different species in allopolyploids over millions of years remains largely unknown. Here, we generate three near-complete genome assemblies, a tetraploid Brachypodium hybridum and its two diploid ancestors, Brachypodium distachyon and Brachypodium stacei. We detect high degrees of sequence, structural, and epigenetic variations of centromeres at base-pair resolution between closely related Brachypodium genomes, indicating the appearance and accumulation of species-specific centromere repeats from a common origin during evolution. We also find that centromere homogenization is accompanied by local satellite repeats bursting and retrotransposon purging, and the frequency of retrotransposon invasions drives the degree of interspecies centromere diversification. We further investigate the dynamics of centromeres during alloploidization process, and find that dramatic genetics and epigenetics architecture variations are associated with the turnover of centromeres between homologous chromosomal pairs from diploid to tetraploid. Additionally, our pangenomes analysis reveals the ongoing variations of satellite repeats and stable evolutionary homeostasis within centromeres among individuals of each Brachypodium genome with different polyploidy levels. Our results provide unprecedented information on the genomic, epigenomic, and functional diversity of highly repetitive DNA between closely related species and their allopolyploid genomes at both coarse and fine scale.